Determinan Keputusan Petani menjadi Peserta Asuransi Usaha Tani Padi di Kabupaten Karawang - Wulandari, Tatu Nia; Nurmalina, Rita; Pasaribu, Sahat M (Analisis Kebijakan Pertanian, 2025)
The main problem faced by insurance companies in Indonesia in implementing agricultural insurance is the low awareness of farmers to participate in the insurance scheme. To encourage farmers’ participation in Rice Crop Insurance (AUTP) scheme in Indonesia, the government provides a premium subsidy of 80%. AUTP as a protection scheme for farmers should be implemented continuously to support a sustainable increase in rice production. This research aimed to investigate the determinants of farmers’ decisions to participate in the AUTP scheme. Data were collected from 110 rice farmers through interviews using structured questionnaires, from January to April 2021 in Karawang Regency, West Java Province. Logistic regression analysis was used in this study. Land area, land ownership, income, insurance knowledge, and participation in insurance socialization were variables that influence farmers’ decision to become participants in AUTP. Farmers’ knowledge and participation in socialization provided a higher opportunity for farmers to become AUTP participants. To increase farmers’ participation in AUTP, this study suggests that the Government carries out structured and systematic socialization, promotion, and advocacy related to AUTP regularly and comprehensively. Efforts to increase media of publication as sources of information are needed to increase farmers’ knowledge about AUTP.